Who needs literacy programs for women in rural Nepal? - Hertzog, Esther (Hagar: Studies in Society and Culture, 2009)
The paper focuses on a development project in rural Nepal aimed at women's empowerment. It argues that this project, like numerous others aimed at women's empowerment, serves the developing organizations and experts rather than the women who are the subjects of such projects. The ethnography was collected in the summer of 1977, while working for an Israeli irrigation company by which I was employed as a gender consultant. It demonstrates how organizations enhance recognition of self-evident need for their help by portraying the women, explicitly or implicitly, as needy and backward. Contrary to this portrayal, I wish to show that these women have ample social and economic competence. Rather than addressing the rural women's lack of economic resources, such projects offer literacy programs that are marginally needed for daily routines. The analysis offers testimony of the built-in failure of critical, postcolonial anthropological theory to contend with its subject matter in a manner that credits the voice and agency it purports to accord. The proposed critique breaks down hierarchical dichotomies embedded in both the assumed gender and colonial distinction, affirming the ethical agenda of domination and subordination.